The place and role of Gorno-Badakhshan Autonomous Region in the state system of Tajikistan - P. B. Parshin (Международная аналитика, 2016)
The paper suggests a description of the place occupied in Tajikistan by the largest and less populated territory of the republic, namely Gorno-Badakhshan Autonomous Region, inhabited mostly by relative to Tajiks Pamiri peoples that possess ethnic and confessional identity of their own and speak about a dozen of Easter Iranian languages. A part of the region is also inhabited by a small number of nomadic Kyrgyz clans. The role of the region and its population in the history, economic and political development of Tajikistan, especially in post-Soviet period, as well as its future potential and possible threats to its peoples are considered at some length.